PENGARUH UANG ELEKTRONIK TERHADAP KEPUTUSAN BERBELANJA - Dewi Wungkus Antasari (Jurnal Manajemen, 2020)
This research aims to know the effect of electronic money towards the purchashing decision of the people in Kediri in this Industrial Revolution 4.0 era. As we know that so many e-money as financial technology facilities in Indonesia are show up. The author decide to choose GOPAY, OVO, and DANA to be researched. The first reason is, these three e-money are permissibled by Bank Indonesia as Central Bank In Indonesia. Second, GOPAY, OVO, and DANA are the most used e-money in Kediri. They give a lot of promotion for their costumer in so many department stores in Kediri. This reaserach method is qualitative research. The author directly researching on the department store and the people who did the purchasing method with these three electronic money.